DIRECTIONALITY TYPES AND FREQUENCY OF REPAIRS IN SIMULTANEOUS INTERPRETING. (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
Abstract: This article explores the concept of directionality in simultaneous interpretation, focusing on the challenges of categorizing different types of translation and their specific characteristics. It reviews existing research by both local and international scholars, examining the diverse perspectives on directionality in simultaneous interpretation. The study aims to analyze these viewpoints, refine our understanding of the issue, and present a unique perspective on the complexities involved.